COVID-19: Underlying Adipokine Storm and Angiotensin 1-7 Umbrella - Méry, Geoffroy; Epaulard, Olivier; Borel, Anne-Laure; Toussaint, Bertrand; Le Gouellec, Audrey (Frontiers in Immunology, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the third coronavirus leading to a global health outbreak. Despite the high mortality rates from SARS-CoV-1 and Middle-East respiratory syndrome (MERS)-CoV infections, which both sparked the interest of the scientific community, the underlying physiopathology of the SARS-CoV-2 infection, remains partially unclear. SARS-CoV-2 shares similar features with SARS-CoV-1, notably the use of the angiotensin conversion enzyme 2 (ACE2) as a receptor to enter the host cells. However, some features of the SARS-CoV-2 pandemic are unique. In this work, we focus on the association between obesity, metabolic syndrome, and type 2 diabetes on the one hand, and the severity of COVID-19 infection on the other, as it seems greater in these patients. We discuss how adipocyte dysfunction leads to a specific immune environment that predisposes obese patients to respiratory failure during COVID-19. We also hypothesize that an ACE2-cleaved protein, angiotensin 1-7, has a beneficial action on immune deregulation and that its low expression during the SARS-CoV-2 infection could explain the severity of infection. This introduces angiotensin 1-7 as a potential candidate of interest in therapeutic research on CoV infections.